Being of two minds: an ultimatum experiment investigating affective processes - Dominique Cappelletti; Werner Güth; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We experimentally investigate how affective processes influence proposers' and responders' behaviour in the Ultimatum Game. Using a dualsystem approach, we tax cognitive resources through time pressure and cognitive load to enhance the influence of affective processes on behaviour. We find that proposers offer more under time pressure and this seems to be due to strategic considerations rather than to other-regarding concerns. We also find that responders are more likely to reject under time pressure. Surprisingly, both proposers and responders appear to be unaffected by cognitive load manipulation.
Keywords: C72; C78; C91; 330; Ultimatum game; dual-system theories; time pressure; cognitive load; experimental economics.; Verhandlungstheorie; Zeit; Kognition; Test